Litigation Against Clients and Audit Report Lag Effect: The Moderating Role of State Ownership and Audit Committees with Legal Expertise in Indonesia - Muhammad Jordan Bastomi; Herera Deviana Pratiwi (Green Publisher Indonesia, 2026)
This study aims to examine the effect of litigation against clients on audit report lag (ARL) and analyze the role of state ownership and audit committees with legal expertise as moderating variables. This study uses a quantitative approach with secondary data sourced from the Directory of Decisions of the Supreme Court of the Republic of Indonesia and audited financial reports of companies listed on the Indonesia Stock Exchange (IDX). The research population includes all companies listed on the IDX during the 2021–2023 period, with a final sample of 628 companies obtained through purposive sampling after the outlier elimination process. Hypothesis testing was conducted using Tobit regression, considering the variables of litigation delay, number of litigation claims, and monetary amount of litigation claims, as well as including the moderating variables of state ownership and audit committees with legal expertise. The results show that litigation delays and the monetary amount of litigation claims have a positive effect on audit report lag, while the number of litigation claims has no effect on audit report lag. Furthermore, the existence of an audit committee with legal expertise has been shown to weaken the effect of litigation delays on audit report lag, while state ownership does not weaken the effect of litigation delays on audit report lag. These findings provide empirical contributions to expanding the audit literature related to litigation risk and emphasize the importance of corporate governance mechanisms in mitigating audit reporting delays, particularly in Indonesian companies post-COVID-19 pandemic.